Metallic constituents in water samples from the Michu and Langat Rivers - Batcha, F.K.; Agamuthu, Pariatamby; Ibrahim, Shaliza (Faculty of Science, University of Malaya, 2004)
The concentrations of the metals Cr, Mn, Fe, Ni, Cu, Zn, Pb, Mg, Ba, K and Cd in water samples from the Michu and Langat Rivers were measured using the Inductively-Coupled Plasma (ICP) technique. Samples were taken at six locations on the rivers, on five different days between May and July of 1999 in relation to the closure of the Ampang Municipal Landfill. Mn, Fe, Zn, Mg, Ba and K were detected in all the samples. Cr, Cu and Cd were present in most samples while Ni and Pb were only found in six and four samples, respectively, out of a total of 35 samples analyzed for each metal. With a few exceptions, samples from locations furthest away from the leachate source were often lower in the metallic content compared to other locations. There was no consistent indication of the effect of time from landfill closure on metal concentration.